Attention difficulties and physical dysfunction common in children with complex congenital malformations: a study of preschool children with VACTERL association. (24th September 2018) - Kassa, A‐M; Dahl, M; Strinnholm, M; Engstrand Lilja, H
Abstract: Aim: Knowledge on the neurodevelopmental and physical function in children with vertebral defects, anorectal malformations, cardiac defects, tracheo‐oesophageal fistula, renal and limb malformations (VACTERL) is scarce. We evaluated Swedish preschool children with VACTERL and identified whether they would need extra support in school. Methods: From 2015 to 2017, we recruited children aged 5–7 with VACTERL association from the paediatric surgical centre at the University Children's Hospital at Uppsala. Neurodevelopmental function was assessed by age‐appropriate intelligence and visual and auditory attention tests, and the children's behaviour and attention were observed by an experienced psychologist. Physical function was evaluated through parental interviews and examinations. Data on patient characteristics, including any surgery and anaesthesia, were extracted from medical records. Results: Of the 13 eligible families, 10 agreed to participate. Intelligence was within the normal range for all children, but attention difficulties were found in eight of the children, requiring adjustments at school, and two of these were later diagnosed with attention deficit hyperactivity disorder. All children had physical dysfunctions that affected their daily nutrition, bowel or bladder functions. Conclusion: Attention difficulties and physical dysfunction were common in Swedish preschool children aged 5–7 with VACTERL and they would need support and adjustments when they started school.